LOST Opportunities
XIV, 298 p.
Keywords: Learning in informal settings is attracting growing attention from policymakers and researchers, yet there remains, at the moment, a dearth of literature on the topic. Thus this volume, which examines how science and mathematics are experienced in everyday and out-of-school-time (OST) settings, makes an important contribution to the field of the learning sciences. Conducting research on OST learning requires us to broaden and deepen our conceptions of learning as well as to better identify the unique and common qualities of different learning settings. We must also find better ways to analyze the interplay between OST and school-based learning. In this volume, scholars develop theoretical structures that are useful not only for understanding learning processes, but also for helping to create and support new opportunities for learning, whether they are in or out of school, or bridging a range of settings. The chapters in this volume include studies of everyday and situated processes that facilitate science and mathematics learning. They also feature new theoretical and empirical frameworks for studying learning pathways that span both in- and out-of-school time and settings. Contributors also examine structured OST programs in which everyday and situated modes of learning are leveraged in support of more disciplined practices and conceptions of science and mathematics. Fortifying much of this work is a leading focus on educational equity—a desire to foster more socially supportive and intellectually engaging science and mathematics learning opportunities for youth from historically non-dominant communities. Full of compelling examples and revealing analysis, this book is a vital addition to the literature on a subject with a fast-rising profile. I believe that the studies represented in this volume will move our work forward as we seek to understand better which social ecologies support -- indeed, ratchet up -- learning and givemeaning for youth, especially those from non-dominant communities. Kris Gutiérrez, University of Colorado at Boulder For someone who has long been interested in afterschool educational activities as a promising supplement to formal, in-school education, this book provides rich opportunities to think about the promise and the problems that such programs offer to those concerned with the infusion of science into the learning and development of their participants. Mike Cole, University of California, San Diego.